OPTIMALISASI SISTEM INFORMASI AUDIT INTERNAL DALAM MENINGKATKAN MUTU PERGURUAN TINGGI - Ratna Imanira Sofiani (Universitas Sahid Surakarta, 2020)
UNIKOM is a university in the field of technology, information and communication which continuously improves quality, efficiency and products to be able to compete. The not yet integrated quality assurance system is the basis for the implementation of this research with the aim of knowing the current system, making system design, analyzing and testing the system to optimize the information system. For the system development method using several tools such as flowmaps, context diagrams and data flow diagrams.The results of research at the QA Directorate of the IKA Directorate concluded that the quality assurance information system is expected to help manage Lecturer data, teaching data, lecture data and e-SPMI more quickly and can reduce errors in the data recording process and reduce errors in reporting.